Praktik Serba 10.000 di Aplikasi Shopee menurut Hukum Ekonomi Syariah dan Peraturan Menteri Sosial Nomor 12 Tahun 2019 tentang Penyelenggaraan Undian Gratis Berhadiah: The Practice of All 10,000 in the Shopee Application according to Sharia Economic Law and Regulation of the Minister of Social Affairs Number 12 of 2019 concerning the Implementation of Free Draws with Prizes - Sya'bana, Ramdani Mugni (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2022)
This study aims to determine the mechanism of the program which is then linked to the Regulation of the Minister of Social Affairs Number 12 of 2019 concerning the Implementation of Free Lottery with Prizes. Based on the results of the study, it can be concluded that the program can be followed by Shopee users and follows the applicable terms and conditions, when viewed from the process there are several elements of interrelated contracts, such as buying and selling, gharar, gambling, sweepstakes, and prizes. Shopee all 10,000 contains elements of gharar but gharar yasir, or a little gharar. After further analysis, this is included in the practice of lottery prizes. The prize itself is included in the tabarru contract, which if there is gharar yasir in the tabarru contract, it is allowed. The practice of all 10,000 in the Shopee application which is linked to the Minister of Social Affairs Regulation Number 12 of 2019 concerning the Organizing of Free Sweepstakes with Prizes, the researcher sees the suitability between Shopee of 10,000 and the regulation, because the important things that have been regulated by the regulation have been carried out by Shopee. Penelitian ini bertujuan untuk mengetahui mekanisme program tersebut kemudian dihubungkan dengan Peraturan Menteri Sosial Nomor 12 tahun 2019 Tentang Penyelenggaraan Undian Gratis Berhadiah. Berdasarkan hasil penelitian, dapat disimpulkan bahwa program tersebut dapat diikuti oleh pengguna Shopee serta mengikuti syarat dan ketentuan yang berlaku, jika dilihat dari prosesnya terdapat beberapa unsur akad yang saling berkaitan, seperti jual beli, gharar, judi, undian, serta hadiah. Shopee serba 10.000 mengandung unsur gharar akan tetapi gharar yasir, atau gharar yang sedikit. Setelah dianalisa lebih jauh ini termasuk ke dalam praktik undian berhadiah. Hadiah sendiri termasuk akad tabarru’ yang mana jika terdapat gharar yasir dalam akad tabarru’ maka diperbolehkan. Praktik serba 10.000 di aplikasi Shopee yang dihubungkan dengan Peraturan Menteri Sosial Nomor 12 Tahun 2019, ada kesesuaian antara Shopee serba 10.000 dengan Peraturan tersebut, karena hal-hal penting yang sudah diatur oleh peraturan tersebut sudah dijalankan oleh pihak Shopee